Concentrations of Diazepam and Nordiazepam in 1000 Blood Samples From Apprehended Drivers—Therapeutic Use or Abuse of Anxiolytics?. (June 2013) - Jones, Alan W.; Holmgren, Anita
Using an in-house forensic toxicology database, we selected 1000 cases of driving under the influence of drugs (DUIDs) over a 12-month period if diazepam (D) and nordiazepam (ND) were both present in the blood samples. Quantitative analysis of D and ND in blood was done by solvent extraction (butyl acetate) and capillary column gas chromatography (GC) with a nitrogen–phosphorous (N-P) detector. The limits of quantitation of this analytical method for D and ND in blood were 0.05 mg/L. The correlation between D and ND concentrations in blood was statistically significant ( r = .58, P < .001), as expected for a parent drug and its primary metabolite. However, the frequency distributions were markedly skewed to the right with mean (median) and highest concentrations of 0.37 (0.20) and 6.1 mg/L for D and 0.39 (0.20) and 5.6 mg/L for ND. The mean (median) total concentration (D + ND) was 0.76 mg/L (0.50 mg/L), and the concentration ratios D/ND and ND/D were 1.29 (median 0.95) and 1.41 (median 1.06), respectively. In 90 cases (9%), the concentration of D in blood exceeded 0.83 mg/L, which corresponds to an upper therapeutic limit in plasma (∼1.5 mg/L), assuming a plasma/blood distribution ratio of 1.8:1.